Controladores PID auto-ajustável e nebuloso aplicados em plantas industriais - Guimarães, Felipe de Azevedo (2007)
With the globalization and the competitiveness in all the levels of the industrial sector, the final product quality search became higher. On the other hand, energy saving became another important factor in modern industry. The consumption of electric energy in the industrial sector represents 45.5% of the total consumption of the country. The motor force represents most of this consumption, arriving to be superior of 80% in the textile, paper and cellulose sectors. This work presents two strategies of control, auto-adjustable PID and fuzzy controller, the objectives are a better final product quality and the energy saving. Ventilation and compression industrials process are used in this work. An analysis of limit cycles’ presence through the descriptive function of the fuzzy controller is carried through, providing a previously validation of fuzzy controller’s parameters by simulations, saving time in the adjust phase. Set-point changes are easily made and on-line, still the process is running, in the two considered controllers. Comparisons of energy consumption are made between the conventional strategies and the two strategies considered in this work.